PENGARUH PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, DAN LABA AKUNTANSI TERHADAP RETURN SAHAM (Study Empiris Pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2016ï€2020) - Komalasari, Weni; Tanjung, Rudy; Awaludin, Muryan (JURNAL MITRA MANAJEMEN, 2024)
Food and beverage companies are included in the consumer goods producer sub-sector whose business is to produce healthy and diverse food and beverages for consumers. Food and beverage companies face a lot of competition in maximizing their performance. The purpose of this study was to examine the effect of sales growth, company size, and accounting profit on company stock returns (empirical study on food and beverage sub-sector companies listed on the Indonesian stock exchange in 2016-2020). The sample was determined based on the purposive sampling method. The number of samples taken in this study were 14 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange in 2016-2020. This study uses multiple linear regression analysis assisted by the Eviews 10 program, which includes the classical assumption test, as well as the partial test (t) with a significance level (Î±) = 5 percent. Based on the results of data processing, it was found that company size had a negative and insignificant effect on stock returns, sales growth had a positive effect on stock returns, and accounting profit had a positive and significant effect on stock returns.Â Keywords: Sales Growth, Company Size, Accounting Profit, Stock ReturnÂ